Association between Dysfunctional Beliefs and Coping Strategy among Persons Suffering from Substance Use Disorder - Prosenjit Ghosh; Saptarshi Paul Choudhury; Subho Panja (Annals of Indian Psychiatry)
Background: Substance use seems to be related to the dysfunctional beliefs of an individual. People with dysfunctional beliefs use maladaptive coping methods in stressful situations and can start using substance which might ultimately lead to substance use disorder. Aims and Objectives: This study was done to evaluate the various sociodemographic variables and illness parameters in persons with substance use disorder and their association with important subscales of COPE, to find out the association between DAS and COPE and also to assess the dysfunctional beliefs and attitudes in persons with SUD and the coping methods used in terms of stress. Materials and Methods: The population of this descriptive and cross-sectional study were 44 patients who were admitted under psychiatry ward and consented to the study. The data were collected using the socio-demographic Information Form, The Dysfunctional Attitude Scale (DAS) and the Coping Assessment Questionnaire (COPE). DAS: It is a forty-item scale. 40-280 is the score range. COPE: It is a questionnaire which has 60 questions distributed over 15 sub-scales. Statistical Analysis: “Statistical Package for the Social Sciences (SPSSv22) (SPSS Inc., Chicago, USA)” has been used for analyzing the values. For continuous variables standard deviation has been calculated along with the mean. For categorical variables, percentages and Fisher’s Exact have been used. Results: Statistically significant differences were found in the average scores of restraint coping, turning to religion, seeking emotional and social support and mental disengagement depending on the different reasons for reusing the substance (P=0.015, 0.041, 0.028, 0.033 respectively). There was a negative correlation of Dysfunctional Coping sub-scale of COPE (focus on and venting of emotions) with varied attitude sub-scale (r= -0.373, P=0.013) of DAS and DAS total (r= -0.307, P=0.043). Varied attitude subscale of DAS was positively correlated with Substance Use of Dysfunctional Coping sub-scale of COPE (r= +0.304, P=0.045) whereas Need for Approval sub-scale of DAS showed negative association (r=-0.451, P=0.002) with regards to one item (Positive Reinterpretation and Growth) of Emotion Focused Coping sub-scale of COPE. Individuals who started using substance between 21-25 years of age scored highest in varied attitude subscale (mean score=92.00) and in autonomous attitude subscale (mean score=34.60) of DAS. When we assessed various problem focused coping strategies using COPE scale, it was found that most of the people (n=37, 84%) scored in the range of 12-16 which was in the planning subscale compared to other subscales of problem focused coping. Conclusion: From our study, we can opine that screening of dysfunctional attitude and maladaptive coping in the vulnerable population may help in preventing and reducing substance use and decrease the number of relapses.